Interpretation and tour leadership principles and practices of tour guiding - Chowdhary, Nimit
"Interpretation and Tour Leadership: Principles and Practices of Tour Guiding is a complete manual to tour guiding that is based on the author’s first-hand experience of training more than 3000 tour guides. With a practical hands-on focus, it guides the reader through the key roles and responsibilities of a tour guide from interpretation techniques, leading visitors in difference scenarios, dealing tricky situations to setting up a tour guiding business. Packed with real life international case studies, each chapter follows a thorough pedagogic structure which includes features such as learning objectives, key terms, checklists, tips, discussion questions and activities, and further reading." --